Tinkering with responsive caring in disabled children's healthcare: Implications for training and practice - Barbara E. Gibson; Yani Hamdani; Bhavnita Mistry; Anne Kawamura (SSM: Qualitative Research in Health, 2023)
Health professional education has traditionally relied on the acquisition of vertical expertise whereby learners apply top-down principles and methods to develop clinical skills. In this critical qualitative study, we examined horizontal processes of “knotworking” and “tinkering” in the development of expertise amongst clinicians and trainees in a children's rehabilitation outpatient clinic. Using ethnographic methods of observation, interviews and group dialogues, the study explored what constitutes “good” child healthcare, the risks of separating humanistic from biomedical care, and how discursive assumptions and conventions shaped learning and practices. Our analyses identified processes of responsive caring that integrated medical and humanistic imperatives into transposable, dynamic repertoires through which clinicians could pivot in response to child and family needs and priorities, resource access, and socio-material contexts. We discuss the challenges for teaching and mentoring medical trainees who have to both learn and unlearn particular practices in their efforts to develop responsive expertise.